STOCK DYNAMICS OF HORSE MACKEREL, MEGALASPIS CORDYLA (LINNAEUS) ALONG NORTHWEST COAST OF INDIA - JAISWAR, A. K.; BIRADAR, R. S.; GULATI, D. K. (Journal of Indian Fisheries Association, 2015)
The stock dynamics of horse mackerel, Megalaspis cordyla, alongthe northwest coast of India has been studied using length frequencydata recorded from commercial landings and trawl catches of researchcum-training vessel M.F.V. Saraswati. The growth parameters for thisspecies has been estimated to be L==54 em and K=0.49 per annum. Thenatural and fishing mortality for the stock have been worked out to be0.93 and 0.91 per annum respectively. The study indicated that thestock is fished at a safer fishing mortality level F 0 .1, lower than Fmsylevel.